Evaluation of Book Collection at the Reading Community of 'Pinjam Pustaka' - Rifanto, Dayu; Burdam, Grace Jaquline; Titiahy, Gres; Christina, Pretty; Sulaiman, Arfan Amran (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
‘Pinjam Pustaka,’ a reading community in Sorong City, Southwest Papua, has been a cornerstone for reading habits since January 2021. This study explores the essence of 'Pinjam Pustaka,' seeking to evaluate its book collection to ensure its relevance and suitability for readers of all ages and backgrounds. The study reveals that this reading community offers a diverse array of materials, including textbooks, encyclopedias, novels, and comics, catering to those who lack access to such resources. It also supports self-learning and non-formal education, adapting to the digital age. With its collection continuously growing through donations, 'Pinjam Pustaka' underscores the importance of evaluating children's books to meet the community's changing needs. In 2022, the reading community saw about 720 visitors, primarily children, underlining its significance in the community. A comprehensive book evaluation in 2023, involving four researchers, classified books across seven reading levels and found 1.365 books. This process revealed a balanced distribution between early and beginning readers (43%) and intermediate to advanced readers (57%), suggesting the potential for broader engagement activities. This evaluation ensures that every reader finds suitable material and paves the way for expanding the reading community's appeal beyond its young primary audience.